Factors that influence primary school teachers’ self-efficacy in online teaching - Yap, Chiou Shum; Abdullah, Melissa Ng Li Yen (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2022)
Factors that influence primary school teachers’ self-efficacy in online environment are still seldom researched. There are needs to determine these factors to improve online teaching, which is a new norm. The aims of this study were to evaluate the level of teachers’ self-efficacy in online teaching and to identify the factors that influence it. This was a quantitative study with survey method that involved 155 primary school teachers in Lenggong Zone, Hulu Perak District. Simple random sampling technique was used for sampling purposes. Teachers’ self-efficacy was measured by the Teachers’ Self-Effiacay Scale while factors tthat influence teachers’ self-efficacy was gauged by the Sources of Influence on Teachers’ Self-Efficacy Scale. The factors measured include mastery experience, vicarious experience, verbal persuasion, physiological arousal and contextual factor. Data were analysed with descriptive and inferential statistics. Findings show that primary school teachers have got high self-efficacy in online teaching. Multiple linear regression analysis revealed that mastery experience, vicarious experience, verbal persuasion and physiological arousal factors have got significant influence on teachers’ self-efficacy in online teaching. Contextual factor was the only factor that did not have significant influence on teachers’ self-efficacy in online teaching. Findings of this study can be used to develop intervention programmes to improve teachers’ self-efficacy in online teaching and ultimately to enhance the effectiveness of online teaching in primary schools.